Factors Associated with Poor Glycemic and Lipid Levels in Ambulatory Diabetes Mellitus Type 2 Patients in Asmara, Eritrea: A Cross-Sectional Study. (29th January 2020) - Achila, Oliver Okoth; Ghebretinsae, Millen; Kidane, Abraham; Simon, Michael; Makonen, Shewit; Rezene, Yohannes
Abstract : Objective . There is a dearth of relevant research on the rapidly evolving epidemic of diabetes mellitus (particularly Type 2 diabetes mellitus) in sub-Saharan Africa. To address some of these issues in the Eritrean context, we conducted a cross-sectional study on glycemic and lipid profiles and associated risk factors. Methods . A total of 309 patients with diabetes mellitus on regular follow-up at the Diabetic and Hypertensive Department at Halibet Regional Referral Hospital, Asmara, were enrolled for the study. Data on specific clinical chemistry and anthropomorphic parameters was collected. Chi-squared (χ 2 ) test or Fischer's exact test was used to evaluate the relationship between specific variables. Multivariate logistic regression (backward: conditional) was undertaken to identify the factors associated with increased odds of suboptimal values in glucose and specific lipid panel subfractions. Results . High proportions of patients (76.7%) had suboptimal levels of HbA1c with a mean ± SD of 8.6 % ± 1.36, respectively. In multivariate regression analysis, the likelihood of HbA 1 c ≥ 7 % was higher in patients with abnormal WHR (AOR = 3.01, 95% CI, 3.01 (1.15 – 7.92 = 0.024 )) and in patients without hypertension (AOR = 1.97, 95% CI (1.06–3.56), p = 0.021 ). A unit reduction in eGFR was also associated with HbA 1 c ≥ 7 % (AOR = 0.99, 95% CI (0.98 – 1 = 0.031 )). In a separate analysis, the data shows that 80.9% of the patients had dyslipidemia. In particular, 62.1% of the patients had TC ≥ 200 mg/dL (risk factors: sex, hypertension, and HbA1c concentration), 81.6% had LDL ‐ C ≥ 100 mg/dL (risk factors: sex and hypertension), 56.3% had TG ≥ 150 (risk factors: sex, HbA1c, and waist circumference), 62.8% had abnormal HDL-C (risk factors: waist circumference), 78.3% had non ‐ HDL < 130 mg/dL (risk factors: duration of disease, reduced estimated glomerular filtration rate, and HbA1c), and 45.3% had abnormal TG/HDL (risk factors: sex, age of patient, FPG, and waist circumference). Conclusions . The quality of care, as measured by glycemic and specific lipid targets, in this setting is suboptimal. Therefore, there is an urgent need for simultaneous improvements in both indicators. This will require evidence-based optimization of pharmacological and lifestyle interventions. Therefore, additional studies, preferably longitudinal studies with long follow-up, are required on multiple aspects of DM.